Optimization of media composition for α-amylase production in liquid state fermentation of bitter cassava by aspergillus niger - Khalaf, Abubakir I.; Alam, Md Zahangir; Mohd. Salleh, Hamzah (Journal of Pure and Applied Microbiology, 2014)
A number of media components influencing a-amylase production by Aspergillus niger O103A were studied using local bitter variety of cassava (Manihotes cuelenta) as the main substrate. The media components (cassava, maltose, glucose, yeast extract, urea, NH4NO3, KH2PO4, CaCl2, MgSO4.7H2O, NaCl, and FeSO4.7H2O) were analyzed using Plackett?Burman design. Optimal concentrations of the components contributing positively to enzyme production were further determined using one factor at a time (OFAT) and response surface methodology (RSM) method. Among different nitrogen and supplementary carbon sources tested, yeast extract 2 g/l and maltose 3 g/L were most effective for maximum production of enzyme (49 U/ml). The results show a favorable a-amylase production by applying statistical approach in optimization process.